2023
DOI: 10.3390/jcm12247508
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sleep Disturbances in Latin American Populations and Its Association with Their Socioeconomic Status—A Systematic Review and a Meta-Analysis

F. A. Etindele Sosso,
Filipa Torres Silva,
Rita Queiroz Rodrigues
et al.

Abstract: Background: The worldwide increase in the prevalence and incidence of sleep disturbances represents a major public health issue. Among multiple determinants affecting sleep health, an individual’s socioeconomic status (SES) is the most ignored and underestimated throughout the literature. No systematic review on the relation between SES and sleep health has been previously conducted in Latin America. Methods: PRISMA guidelines were used. Results: Twenty articles were included in the final sample (all cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
(255 reference statements)
0
0
0
Order By: Relevance
“…This is even more important, considering the high prevalence of sleep-related symptoms in Latin America (Bouscoulet et al 2008 ). In this regard, a meta-analysis showed that in Latin America, individuals belonging to a lower socioeconomic level (characterized by low-quality education, lower income, and poor quality work) were more likely to suffer from sleep disorders (Etindele Sosso et al, 2023 ). Recent studies conducted in Peru and El Salvador reported that depression was positively related to insomnia and anxiety (Baños-Chaparro, 2023 ; Mena & Calderón, 2022 ), demonstrating a close relationship between symptoms of sleep disorders, depressive disorders, and generalized anxiety disorders in the Latin American region.…”
Section: Introductionmentioning
confidence: 99%
“…This is even more important, considering the high prevalence of sleep-related symptoms in Latin America (Bouscoulet et al 2008 ). In this regard, a meta-analysis showed that in Latin America, individuals belonging to a lower socioeconomic level (characterized by low-quality education, lower income, and poor quality work) were more likely to suffer from sleep disorders (Etindele Sosso et al, 2023 ). Recent studies conducted in Peru and El Salvador reported that depression was positively related to insomnia and anxiety (Baños-Chaparro, 2023 ; Mena & Calderón, 2022 ), demonstrating a close relationship between symptoms of sleep disorders, depressive disorders, and generalized anxiety disorders in the Latin American region.…”
Section: Introductionmentioning
confidence: 99%